1985
DOI: 10.1063/1.95868
|View full text |Cite
|
Sign up to set email alerts
|

Disordering of Ga1−xAlxAs-GaAs quantum well structures by donor sulfur diffusion

Abstract: We show here, for the first time, that disordering (alloy mixing) on group III sublattice of GaAlAs-GaAs quantum well (QW) structures can be accomplished by the introduction of a group V site substitutional donor impurity. This is achieved by performing donor sulfur diffusions at 850 °C (for varied durations 1 to 14 h) under open-tube conditions in molecular beam epitaxy as well as metalorganic chemical vapor deposition grown GaAlAs-GaAs QW structures. Using simple photoluminescence measurements at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Quantum well intermixing studies of AlGaAs/GaAs heterostructure also indicate that diffusion of species which occupy the group III sublattice is enhanced by the introduction of n-type group IV and group VI dopants. 81,[95][96][97][98] Direct evidence of vacancies using STM have been confirmed in n-type GaAs [99][100][101] and positron annihilation results 102-109 also indicate that n-type doping results in higher concentration of vacancies than is observed in un-doped or p-type GaAs. There are also reports of superdilation of GaAs and InAs with n-type doping and dopant-vacancy complexes have been suggested as the cause for the unexpected increases in lattice parameter at high doping concentrations.…”
Section: Concentration Dependent Si Diffusion In Ingaas Andmentioning
confidence: 94%
“…Quantum well intermixing studies of AlGaAs/GaAs heterostructure also indicate that diffusion of species which occupy the group III sublattice is enhanced by the introduction of n-type group IV and group VI dopants. 81,[95][96][97][98] Direct evidence of vacancies using STM have been confirmed in n-type GaAs [99][100][101] and positron annihilation results 102-109 also indicate that n-type doping results in higher concentration of vacancies than is observed in un-doped or p-type GaAs. There are also reports of superdilation of GaAs and InAs with n-type doping and dopant-vacancy complexes have been suggested as the cause for the unexpected increases in lattice parameter at high doping concentrations.…”
Section: Concentration Dependent Si Diffusion In Ingaas Andmentioning
confidence: 94%
“…By photoluminescence study, it has been shown that enhanced Al interdiffusion in AlGaAs superlattice can be produced by S diffusion through the sample surface. Further, the extent of Al interdiffusion was found to depend on the S concentration [5].…”
Section: Introductionmentioning
confidence: 92%
“…It has been known that mixing in AlGaAs based superlattice can be dramatically enhanced by introducing impurities such as Zn [3], Si [4], S [5] or Se [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the largest blue shifts are observed in samples grown on S-doped InP substrates, which originally had led us to believe that the mechanism responsible for the blue shift was related to IILD. Sulphur is an n-type dopant in the GaInAsP system, thought to substitutionally reside on the group V sublattice, and has been shown to be responsible for IILD in the GaAlAs/GaAs system (Gavrilovic et al 1985, Rao et al 1985, Baba-Ali et a[ 1991. Recently, however, Glew and co-workers (1992) reported that the activation energy for interdiffusion of undoped GaInAs/GaInAsP MQW structures grown on InP substrates, derived from photoluminescence measurements, varies as a logarithmic function of the substrate etch pit density.…”
Section: Multilayer Thermal Stability In Relation To Spatially Varyin...mentioning
confidence: 99%